Design computacional: comunicação do in-visível - Nunes, João Fernando Igansi (2009)
The language is a machine and the design that shapes it, it is another one, as well as the machine is the whole model (Techno Aristotelian) of discourses that conceptualize it: Computational Design in the rule is applying the rule(s). The study of Computational Design: communication of in-visible, presents the configuration of Cultural Interfaces, discourse machines derived from the fixed communication codes (paradigm of manufacturing) in the current state of the informational diagrammatic machines for executable codes (the programming paradigm). This thesis, in the context of the new communication technologies searches to detail the specifics of practice and rhetoric (critical and creative) of the executable codes, those belonging to the creative processes that brought the call of Computational Design: The design resulting from a procedural state generated in the programmed action of the algorithms in their code share operations. Thus, the investigation intersects language, machine and technique, interaction and respective aesthetic results coming from the "culture of software." The idea of building a systematic study on the state of computational design, as well as the quest for the understanding of the latest executable codes communication status, finds its main methodological references in the proposal of John B. Thompson (1995) for analysis of symbolic forms. Under specific circumstances, this proposal organizes the discussion about the nature of the syntax on the current design production on their respective fundaments. Computational Design, on and off line, it is the condition of any additional operation between human systems and machines, and as such it is perceived to sensations and perceptions of both. Within this sphere of the senses, the action of these intelligent languages, matrices that re-match in each logical dimension of events sharing and updates, produce identification and the mapping of the model (ruled by writing) that is perceived (ruled by reading). The "computational thinking" that generated the status of language is logic-processing and production of meta-signs, which is the relationship between the technical content and the technological content of communication that operates and that is based on the theories of post-structuralist authors such as Roland Barthes, Jacques Derrida, Félix Guattari, and the current criticism of Lev Manovich, Katherine Hayles, Florian Cramer, Jean-Pierre Balpe, Margot Lovejoy, Paul Fishwick and Matthew Fuller on the informational and computational media aesthetics. This "computational thinking" which is located in the structures of language algorithms evolves from modern diagrammatic state in the technical imaginary to a technological imaginary emerging from what was known from the twentieth century as Hypermodernism. The observations and analysis of that work were built under the theoretical and practical contributions of Martin Wattenberg, John Maeda, Golan Levin, Benjamin Fry, Markamerica, Mark Napier and Santiago Ortiz